2015
DOI: 10.2337/dc14-2898
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Variability and Diabetes Complications: Does It Matter? Of Course It Does!

Abstract: There is no argument that improving mean levels of glycemic control as judged by assays for glycated hemoglobin (HbA1c) reduces the risks of microvascular complications and cardiovascular disease events in patients with type 1 and type 2 diabetes. However, observations in some trials have suggested that targeting HbA1c to suggested targets may not always result in improved outcomes for people with long-standing type 2 diabetes. The reasons why the glycemic control strategies that primarily use HbA1c in these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
166
2
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(180 citation statements)
references
References 24 publications
1
166
2
11
Order By: Relevance
“…38,56 Patient recall of hypoglycemic events is bias prone. In 15-20-min clinical encounters once every few months, it is important to quickly assess patient's glucose patterns and to act on patterns in addition to addressing any other concerns.…”
Section: Cgm Reports and Data Interpretationmentioning
confidence: 99%
“…38,56 Patient recall of hypoglycemic events is bias prone. In 15-20-min clinical encounters once every few months, it is important to quickly assess patient's glucose patterns and to act on patterns in addition to addressing any other concerns.…”
Section: Cgm Reports and Data Interpretationmentioning
confidence: 99%
“…Landmark clinical trials have shown that lowering HbA1c reduces the risk of development and progression of diabetes complications,1, 2 which has led to a treatment focus on achieving the generally recommended target HbA1c of <7.0% 3. Although controversial,4, 5 in the past decade, a body of evidence has implicated glycaemic variability in the pathogenesis of diabetes complications, suggesting that glycaemic variability should also be considered a target for glucose‐lowering therapies 6, 7. Glycaemic variability refers to acute excursions in blood glucose levels, including hypoglycaemic events and postprandial hyperglycaemia, and may be known by some patients and physicians as daily glucose fluctuations 8.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies assessing effects of more versus less intense glucose lowering for ;5 years recorded mixed results (5,6), with a cardiovascular benefit emerging in only one study during passive followup (7). One potential reason for this discrepancy is that A1C does not reflect glycemic variability (GV), which typically increases with longer duration of type 2 diabetes, mainly due to progressive insulin deficiency (8).…”
mentioning
confidence: 99%